Steel materials

A high-strength steel material with a protective film and specific chemical composition addresses the challenges of hydrogen embrittlement and formability issues, achieving over 1500 MPa tensile strength and enhanced resistance to hydrogen embrittlement in corrosive environments, suitable for automotive applications.

JP7617452B2Active Publication Date: 2025-01-20NIPPON STEEL CORPORATION
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2022576704
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-01-19
Filing Date
2022-01-19
Publication Date
2025-01-20
Estimated Expiration
2042-01-19

AI Technical Summary

Technical Problem

High-strength steel sheets face challenges in maintaining press formability and dimensional accuracy due to decreased ductility and increased susceptibility to hydrogen embrittlement, especially when tensile strength exceeds 1.5 GPa, which is critical for automotive applications requiring both high strength and resistance to hydrogen embrittlement in corrosive environments.

Method used

A steel material with a specific chemical composition and a protective film composed of iron oxide or iron oxyhydroxide, which enhances corrosion resistance and hydrogen embrittlement resistance, is developed. The steel material includes a protective film with a peak intensity of over 250% at a specific diffraction angle and a Cu content ratio of 1.5 or more, ensuring high tensile strength and improved hydrogen embrittlement resistance.

Benefits of technology

The steel material achieves a tensile strength of over 1500 MPa with significantly reduced risk of hydrogen embrittlement, enabling safer application in car bodies and maintaining structural integrity in corrosive environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007617452000007
    Figure 0007617452000007
  • Figure 0007617452000008
    Figure 0007617452000008
  • Figure 0007617452000001
    Figure 0007617452000001
Patent Text Reader

Abstract

This steel material includes a steel sheet base material and a protective film formed at least partially on the surface of the steel sheet base material. The steel sheet base material has a chemical composition containing, in mass%, 0.25-0.65% of C, 0.05-2.00% of Si, 0.30-3.00% of Mn, 0.050% or less of P, 0.0100% or less of S, 0.010% or less of N, 0.010% or less of O, 0.05-1.00% of Cr, and 0.10-1.00% of Cu. The protective film has, when a measurement is performed thereon by an X-ray analysis using CuKα radiation, a peak where the peak intensity is more than 250% at a position where the diffraction angle (2θ) is 35.5±0.5°, when the peak intensity at a position where the diffraction angle (2θ) is 36.6±0.5° is defined as 100%. The steel material has a tensile strength of more than 1500 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a steel material. This application claims priority based on Japanese Patent Application No. 2021-006369, filed on January 19, 2021, the contents of which are incorporated herein by reference. [Background technology]

[0002] In the field of automotive steel sheets, the use of steel sheets with high tensile strength (high-strength steel sheets) is expanding in order to improve both fuel efficiency and crashworthiness against the backdrop of recent stricter environmental regulations and crash safety standards. However, as the strength of steel sheets increases, the press formability of the steel sheets decreases, making it difficult to manufacture products with complex shapes.

[0003] Specifically, as the strength of steel sheets is increased, the ductility of the steel sheets decreases, and when the steel sheets are processed into complex shapes, the steel sheets break at highly processed areas. In addition, as the strength of steel sheets is increased, the residual stress after processing causes springback and wall warping, which deteriorates the dimensional accuracy. Therefore, it is not easy to press-form high-strength steel sheets, especially those with a tensile strength of 780 MPa or more, into products with complex shapes. Although high-strength steel sheets can be easily processed by roll forming instead of press forming, the application of roll forming is limited to parts with a uniform cross section in the longitudinal direction.

[0004] In recent years, therefore, hot stamping technology has been adopted as a technology for press forming difficult-to-form materials such as high-strength steel plates, as disclosed in, for example, Patent Documents 1 to 3. The hot stamping technology is a hot forming technology in which the material to be formed is heated and then formed.

[0005] In this technology, the material is heated before it is formed. Therefore, the steel is soft during forming and has good formability. This allows even high-strength steel plates to be formed with high precision into complex shapes. In addition, with hot stamping technology, the steel is quenched at the same time as it is formed using a press die, so the steel (steel component) has sufficient strength after forming.

[0006] For example, Patent Document 1 discloses that hot stamping technology can impart a tensile strength of 1400 MPa or more to a formed steel member.

[0007] In recent years, countries around the world have set higher CO2 reduction targets, and automobile companies are working to reduce fuel consumption while considering collision safety. In electric vehicles, which are rapidly advancing as well as gasoline-powered vehicles, there is a demand for materials with even higher strength to protect not only passengers but also batteries from collisions and to offset the weight increase. For example, steel members used in automobiles and the like require higher strength (strength exceeding 1.5 GPa) than those described in the above-mentioned Patent Document 1 and those generally used for steel members currently formed by hot stamping.

[0008] However, for many metal materials, various properties deteriorate as the strength increases, and in particular the susceptibility to hydrogen embrittlement increases. It is known that hydrogen embrittlement susceptibility increases for steel components when the tensile strength is 1.2 GPa or more, and there have been cases of hydrogen embrittlement cracking in bolt steel, which has been strengthened ahead of the automotive industry. For this reason, there are concerns that hydrogen embrittlement susceptibility will increase further in hot stamped components with tensile strengths of over 1.5 GPa.

[0009] Steel components used in automobiles are at risk of hydrogen embrittlement cracking due to hydrogen generated by corrosion of the steel during use. As mentioned above, the hydrogen embrittlement sensitivity of steel is extremely high, especially in the strength range of over 1.5 GPa, so it is thought that hydrogen embrittlement can occur even with a small amount of hydrogen caused by minor corrosion. However, it is difficult to design an automobile that completely prevents corrosion of steel. Therefore, in order to apply hot stamped components over 1.5 GPa to the vehicle body to further reduce the vehicle weight, it is necessary to sufficiently reduce the risk of hydrogen embrittlement cracking.

[0010] Regarding high-strength steel materials having a tensile strength exceeding 1.5 GPa, for example, Patent Document 2 discloses a hot press-formed press-formed product having excellent toughness and a tensile strength of 1.8 GPa or more. Patent Document 3 discloses a steel material having an extremely high tensile strength of 2.0 GPa or more, and further having good toughness and ductility. Patent Document 4 discloses a steel material having a high tensile strength of 1.8 GPa or more, and further having good toughness. Patent Document 5 discloses a steel material having an extremely high tensile strength of 2.0 GPa or more, and further having good toughness. However, these steel materials have not been fully studied from the viewpoint of hydrogen embrittlement resistance in a corrosive environment, and further improvement in hydrogen embrittlement resistance is desired.

[0011] For example, Patent Document 6 discloses a structure in which tempered martensite is contained in an area ratio of 50% or more (including 100%) and the remainder is made of ferrite, and the distribution state of precipitates in the tempered martensite is as follows: precipitates having a circle equivalent diameter of 1 to 10 nm are present within 1 μm of the tempered martensite. 2 The precipitates containing V, which are 20 or more per 1 μm and have a circle equivalent diameter of 20 nm or more, are 2Patent Document 6 focuses on a high-strength steel sheet having a tempered martensite single phase or a dual-phase structure consisting of ferrite and tempered martensite, and discloses that adding V as an alloying element to the steel sheet improves stretch flangeability while ensuring hydrogen embrittlement resistance by introducing V carbides and carbonitrides, which act strongly as hydrogen trapping sites, into the martensite with appropriate sizes. However, Patent Document 6 relates to a high-strength cold-rolled steel sheet having a strength of 980 MPa or more before hot stamping. This high-strength cold-rolled steel sheet is not a steel sheet for hot stamping, and Patent Document 6 does not consider mechanical properties such as strength after hot stamping in the case of hot stamping, as well as hydrogen embrittlement resistance. [Prior art documents] [Patent documents]

[0012] [Patent Document 1] Japanese Patent Publication No. 2002-102980 [Patent Document 2] Japanese Patent Application Publication No. 2012-180594 [Patent Document 3] Japanese Patent Publication No. 2012-1802 [Patent Document 4] International Publication No. 2015 / 182596 [Patent Document 5] International Publication No. 2015 / 182591 [Patent Document 6] Japanese Patent No. 4712838 Summary of the Invention [Problem to be solved by the invention]

[0013] The present invention has been made to solve the above problems, and has an object to provide a steel material having high tensile strength and excellent resistance to hydrogen embrittlement in a corrosive environment. [Means for solving the problem]

[0014] The present invention relates to the following steel material.

[0015] (1) A steel material according to one embodiment of the present invention has a steel plate substrate and a protective film formed on at least a part of a surface of the steel plate substrate, the chemical composition of the steel plate substrate being, in mass%, C: 0.25 to 0.65%, Si: 0.05 to 2.00%, Mn: 0.30 to 3.00%, P: 0.050% or less, S: 0.0100% or less, N: 0.010% or less, O: 0.010% or less, Cr: 0.05 to 1.00%, Cu: 0.10 to 1.00%, and %, Ti: 0-0.10%, B: 0-0.0100%, Mo: 0-1.00%, Ni: 0-1.00%, Nb: 0-0.10%, V: 0-1.00%, Ca: 0-0.010%, Mg: 0-0.010%, Al: 0-1.00%, Sn: 0-1.00%, W: 0-1.00%, Sb: 0-1.00%, Zr: 0-1.00%, Co: 0-1.00%, REM: 0-0.30%, and the balance: Fe and impurities; the protective film is mainly composed of iron oxide and iron oxyhydroxide and contains Fe, O, and H in a total amount of 70 mass% or more; In an X-ray analysis of the protective film measured using CuKα radiation, the protective film has a peak at a diffraction angle (2θ) of 35.5±0.5°, the peak intensity of which exceeds 250%, when the peak intensity at a diffraction angle (2θ) of 36.6±0.5° is taken as 100%, and the ratio of the maximum Cu content in the protective film to the Cu content in the steel sheet substrate is 1.5 or more; The tensile strength is greater than 1500 MPa. [2] In the steel material described in [1] above, the protective film may be formed on the entire surface of the steel plate base material. [3] In the steel material described in [1] above, a corrosion-resistant coating may be formed on a portion of the surface of the steel plate substrate where the protective film is not formed. [4] In the steel material described in [3] above, a corrosion-resistant coating may be formed on two surfaces of the steel plate substrate perpendicular to the plate thickness direction, and a protective film may be formed on two surfaces of the steel plate substrate parallel to the plate thickness direction. [5] In the steel material according to the above [3] or [4], the corrosion-resistant coating may be an Al-Fe-based coating or a Zn-Fe-based coating. 。 Effect of the Invention

[0016] According to the above-mentioned aspect of the present invention, it is possible to provide a steel material having high tensile strength and excellent resistance to hydrogen embrittlement in a corrosive environment. [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is a schematic diagram showing an example of a steel material according to the present embodiment. [Diagram 2] FIG. 4 is a schematic diagram showing another example of a steel material according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The present inventors have investigated the influence of corroded structures and steel materials on these properties in order to obtain a steel material having high tensile strength and excellent resistance to hydrogen embrittlement in a corrosive environment. As a result, the following findings were obtained.

[0019] Most of the commonly used steel plates that have a tensile strength of about 1.5 GPa (1500 MPa) after heat treatment, including quenching such as hot stamping, contain about 0.20 mass% C, which ensures strength after heat treatment.

[0020] (a) In order to further reduce the weight of the vehicle body, the inventors conducted a detailed study to obtain a steel material having a high strength of more than 1.5 GPa after heat treatment by increasing the C content. As a result, it was found that an ultra-high strength of more than 1.5 GPa in tensile strength can be obtained after heat treatment including quenching such as hot stamping by setting the C content to 0.25 mass% or more. On the other hand, as the tensile strength is increased to more than 1.5 GPa, the hydrogen embrittlement susceptibility increases, and there was a concern about the risk of hydrogen embrittlement cracking due to hydrogen generated in the corrosive environment during use of the vehicle.

[0021] (b) The present inventors have discovered that in a high-strength steel material having a tensile strength of more than 1.5 GPa, hydrogen embrittlement in a corrosive environment can be suppressed by forming a protective film with excellent corrosion resistance on the surface of the steel plate substrate.

[0022] Based on the above findings, the inventors have developed a steel material with significantly improved hydrogen embrittlement resistance in a corrosive environment and a tensile strength of more than 1.5 GPa. Such a steel material has high strength but a low risk of hydrogen embrittlement, making it safer for use in vehicle bodies.

[0023] Hereinafter, each requirement of the steel material according to one embodiment of the present invention (steel material according to this embodiment) will be described in detail.

[0024] (A) Steel material As shown in FIG. 1, a steel material 1 according to this embodiment has a steel plate substrate 11 having a predetermined chemical composition, and a protective film 12 formed on the surface of the steel plate substrate 11 and having excellent corrosion resistance. Moreover, the protective film 12 of the steel material 1 according to this embodiment contains a large amount of Fe3O4, and in an X-ray analysis (X-ray diffraction method) measured using CuKα radiation, when the peak intensity at a diffraction angle (2θ) of 36.6±0.5° is taken as 100%, it has a peak at a diffraction angle (2θ) of 35.5±0.5° whose peak intensity exceeds 250%. However, although the protective film 12 is formed only on one surface of the steel sheet substrate 11 in FIG. 1, it may be formed on the entire surface. In addition, a portion of the surface of the steel sheet substrate 11 may be covered with the corrosion-resistant coating 13 (the corrosion-resistant coating 13 is formed on the portion of the surface), and the other surface may be covered with the protective film 12 (the protective film 12 is formed on the other surface). In other words, a portion of the surface of the steel sheet substrate 11 may be covered with the protective film 12, and the portion not covered with the protective film 12 may be covered with the corrosion-resistant coating 13. For example, as shown in FIG. 2, a corrosion-resistant coating 13 may be formed on two surfaces of a steel plate substrate 11 perpendicular to the plate thickness direction, and a protective film 12 may be formed on two surfaces of the steel plate substrate 11 parallel to the plate thickness direction (e.g., cut end surfaces of the steel plate substrate 11). The steel material 1 according to this embodiment is formed by hot stamping in many cases, and the steel material 1 can also be called a hot stamped body or a hot stamped member. Each of these will be explained below.

[0025] (A1) Steel plate base material The steel plate substrate 11 included in the steel material 1 according to this embodiment has a predetermined chemical composition. Specifically, the chemical composition of the steel plate substrate 11 is, in mass%, C: 0.25-0.65%, Si: 0.05-2.00%, Mn: 0.30-3.00%, P: 0.050% or less, S: 0.0100% or less, N: 0.010% or less, O: 0.010% or less, Cr: 0.05-1.00%, Cu: 0.10-1.00%, Ti: 0-0.10%, B: 0-0.0100%, Mo: 0~1.00%, Ni: 0~1.00%, Nb: 0~0.10%, V: 0~1.00%, Ca: 0~0.010%, Mg: 0~0.010%, Al: 0~1.00%, Sn: 0~1.00%, W: 0~1.00%, Sb: 0~1.00%, Zr: 0~1.00%, Co: 0~1.00%, REM: 0~0.30%, and the balance: Fe and impurities. The reasons for limiting each element are as follows. Here, the chemical composition of the steel sheet substrate 11 refers to the chemical composition of a portion (e.g., a position 1 / 4 of the thickness from the surface of the steel sheet substrate 11) excluding the protective film 12 on the surface (or the corrosion-resistant coating 13 if there is no protective film 12 and the corrosion-resistant coating 13 is formed). Hereinafter, % regarding the content is mass % unless otherwise specified.

[0026] C: 0.25-0.65% C is an element that enhances the hardenability of steel and improves the strength of the steel material obtained after quenching such as hot stamping. If the C content is less than 0.25%, it is difficult to ensure sufficient strength (over 1.5 GPa) in the steel material after quenching (hot stamping). Therefore, the C content is set to 0.25% or more. The C content is preferably set to 0.28% or more, 0.31% or more, or 0.33% or more. On the other hand, if the C content exceeds 0.65%, the strength of the steel material after quenching becomes excessively high, and hydrogen embrittlement resistance decreases significantly. Therefore, the C content is set to 0.65% or less. The C content is preferably set to 0.60% or less, 0.55% or less, 0.50% or less, 0.45% or less, or 0.40% or less.

[0027] Silicon: 0.05 to 2.00% Silicon is an effective element for improving the hardenability of steel and stably ensuring the strength of the steel material after hardening. Silicon is also an effective element for forming a tight scale with good adhesion during the heat treatment described below. Such a tight scale can be used as a base for a protective film with excellent corrosion resistance. To obtain this effect, the silicon content must be 0.05% or more. The silicon content is preferably 0.10% or more, more preferably 0.15% or more, 0.25% or more, or 0.35% or more. On the other hand, if the Si content in steel exceeds 2.00%, the heating temperature required for austenite transformation during heat treatment (quenching) becomes significantly high. This may increase the cost required for heat treatment or cause ferrite to remain during heating, reducing the strength of the steel. Therefore, the Si content is set to 2.00% or less. The Si content is preferably set to 1.50% or less, 1.20% or less, 0.80% or less, or 0.60% or less.

[0028] Mn: 0.30-3.00% Mn is an extremely effective element for improving the hardenability of steel and stably ensuring strength after hardening. Mn also lowers the Ac3 point and promotes lowering the hardening temperature. However, if the Mn content is less than 0.30%, the effect is insufficient. Therefore, the Mn content is set to 0.30% or more. The Mn content is preferably set to 0.40% or more, 0.50% or more, 0.60% or more, 0.70% or more, or 0.80% or more. On the other hand, if the Mn content exceeds 3.00%, the hydrogen embrittlement resistance of the steel material after quenching deteriorates. Therefore, the Mn content is set to 3.00% or less. The Mn content is preferably set to 2.50% or less, more preferably 1.50% or less, 1.20% or less, 1.00% or less, 0.90% or less, or 0.80% or less.

[0029] P:0.050% or less P is an element that reduces the hydrogen embrittlement resistance of steel after quenching. In particular, when the P content exceeds 0.050%, the hydrogen embrittlement resistance is significantly reduced. Therefore, the P content is limited to 0.050% or less. The P content may be limited to 0.020% or less, 0.010% or less, or 0.006% or less. Since a small P content is preferable, it may be 0%, but from the viewpoint of cost, it may be 0.001% or more.

[0030] S: 0.0100% or less S is an element that reduces the hydrogen embrittlement resistance of steel after quenching. In particular, when the S content exceeds 0.0100%, the hydrogen embrittlement resistance is significantly reduced. Therefore, the S content is limited to 0.0100% or less. The S content is preferably limited to 0.0050% or less. The S content may be limited to 0.0020% or less, 0.0010% or less, or 0.0006% or less. Since a small S content is preferable, it may be 0%, but from the viewpoint of cost, it may be 0.0001% or more.

[0031] N: 0.010% or less N is an element that reduces the hydrogen embrittlement resistance of steel after quenching. In particular, when the N content exceeds 0.010%, coarse nitrides are formed in the steel, and the hydrogen embrittlement resistance is significantly reduced. Therefore, the N content is set to 0.010% or less. The N content may be limited to 0.008% or less, 0.006% or less, or 0.004% or less. There is no need to particularly limit the lower limit of the N content, and it may be 0%, but setting the N content to less than 0.0002% increases the steelmaking cost and is not economically preferable. Therefore, the N content may be set to 0.0002% or more, 0.0008% or more, or 0.001% or more.

[0032] O: 0.010% or less O is an element that reduces the hydrogen embrittlement resistance of steel after quenching. In particular, when the O content exceeds 0.010%, coarse nitrides are formed in the steel, and the hydrogen embrittlement resistance is significantly reduced. Therefore, the O content is set to 0.010% or less. The O content may be limited to 0.008% or less, 0.006% or less, or 0.004% or less. There is no need to particularly limit the lower limit of the O content, and it may be 0%, but setting the O content to less than 0.0002% increases the steelmaking cost and is economically undesirable. Therefore, the O content may be set to 0.0002% or more, 0.0008% or more, or 0.001% or more.

[0033] Cr: 0.05~1.00% Cr is an effective element for improving the hardenability of steel and stably securing the strength of the steel material after hardening. It is also an effective element for making the scale into a tight scale with good adhesion that can be used as the base of a protective film with excellent corrosion resistance during the heat treatment described below. To obtain this effect, the Cr content must be 0.05% or more. The Cr content is preferably 0.10% or more. On the other hand, if the Cr content exceeds 1.00%, the above effects are saturated and the cost increases. In addition, since Cr has the effect of stabilizing iron carbides, if the Cr content exceeds 1.00%, coarse iron carbides may remain undissolved during the heat treatment of the steel sheet, which may reduce the hydrogen embrittlement resistance of the steel material. Therefore, the Cr content is set to 1.00% or less. In order to reduce the alloy cost, the Cr content is preferably set to 0.80% or less, 0.60% or less, 0.50% or less, or 0.40% or less.

[0034] Cu: 0.10-1.00% Cu is an element effective for improving the hardenability of steel and stably securing the strength of the steel material after hardening. To obtain this effect, it is necessary to contain Cu at 0.10% or more. Cu is also an element that stabilizes the protective film described below, thereby further improving the corrosion resistance. To obtain this effect, the Cu content is preferably 0.18% or more, and more preferably 0.20% or more. The reason why the protective film is stabilized by the inclusion of Cu is not clear, but it is thought that in the early stage of the formation of the protective film, Cu is concentrated on the surface of the steel sheet substrate, and the protective film is grown uniformly and densely, thereby forming a stable protective film in which Cu is partially concentrated. On the other hand, if the Cu content exceeds 1.00%, the above effects are saturated and the cost increases. Therefore, the Cu content is set to 1.00% or less. In order to reduce the alloy cost, the Cu content is preferably set to 0.80% or less, 0.60% or less, 0.50% or less, or 0.30% or less.

[0035] In order to improve various properties (hardenability, strength, hydrogen embrittlement resistance, deoxidization, corrosion resistance, etc.) of the steel material and parts containing this steel material, one or more elements selected from the group consisting of Ti, B, Mo, Ni, Nb, V, Ca, Mg, Al, Sn, W, Sb, Zr, Co and REM may be further contained within the ranges shown below. These elements are optional elements and do not necessarily need to be contained, so the lower limit is 0%.

[0036] Ti: 0 to 0.100% Ti is an element that suppresses recrystallization and forms fine carbides to suppress grain growth when a steel sheet is heated to a temperature of the Ac3 point or higher for heat treatment, thereby making austenite grains finer. Therefore, the inclusion of Ti has the effect of improving the hydrogen embrittlement resistance of the steel. Ti is also an element that suppresses the consumption of B due to the precipitation of BN by preferentially bonding with N in the steel, and promotes the effect of improving hardenability due to B, which will be described later. Therefore, Ti may be included. To obtain the above effects, the Ti content is preferably 0.010% or more, and more preferably 0.015% or more. On the other hand, if the Ti content exceeds 0.100%, the amount of TiC precipitated increases and C is consumed, resulting in a decrease in the strength of the steel material after quenching. Therefore, when Ti is contained, the Ti content is set to 0.100% or less. In order to reduce alloy costs, the Ti content is preferably set to 0.080% or less, 0.060% or less, or 0.030% or less.

[0037] B: 0~0.0100% B is an element that has the effect of dramatically improving the hardenability of steel even in a small amount. In addition, B is an element that segregates at grain boundaries to strengthen the grain boundaries and improve hydrogen embrittlement resistance, and is an element that suppresses the grain growth of austenite when the steel sheet is heated. Therefore, B may be contained. To obtain the above effects, the B content is preferably 0.0005% or more, and more preferably 0.0010% or more. On the other hand, if the B content exceeds 0.0100%, a large amount of coarse compounds precipitates, and the hydrogen embrittlement resistance of the steel material decreases. Therefore, when B is contained, the B content is set to 0.0100% or less. In order to reduce the alloy cost, the B content is preferably set to 0.0080% or less, 0.0050% or less, or 0.0025% or less.

[0038] Mo: 0 to 1.00% Mo is an extremely effective element for improving the hardenability of steel and stably securing the strength of the steel material after hardening. In particular, by including Mo in combination with the above-mentioned B, a synergistic effect of improving hardenability can be obtained. For this reason, Mo may be included. To obtain the above effect, the Mo content is preferably 0.10% or more, and more preferably 0.20% or more. On the other hand, Mo is an element that has the effect of stabilizing iron carbides. If the Mo content exceeds 1.00%, coarse iron carbides remain undissolved when the steel plate is heated, and the hydrogen embrittlement resistance of the steel material after quenching may decrease. In addition, the cost increases significantly. Therefore, when Mo is contained, the Mo content is set to 1.00% or less. In order to reduce the alloy cost, the Mo content is preferably set to 0.80% or less, 0.60% or less, or 0.32% or less.

[0039] Ni: 0 to 1.00% Ni is an effective element for improving the hardenability of steel and stably securing the strength of the steel material after hardening. Therefore, Ni may be contained. To obtain the above effects, the Ni content is preferably 0.10% or more, and more preferably 0.20% or more. On the other hand, if the Ni content exceeds 1.00%, the limit hydrogen content of the steel material decreases. Also, the cost increases significantly. Therefore, when Ni is contained, the Ni content is set to 1.00% or less. To reduce the alloy cost, the Ni content is preferably set to 0.50% or less, more preferably set to 0.25% or less, and even more preferably set to 0.20% or less.

[0040] Nb: 0 to 0.10% Nb is an element that forms fine carbides in steel and improves the hydrogen embrittlement resistance of steel due to the grain refinement effect of the carbides. Therefore, Nb may be contained. To obtain the above effect, the Nb content is preferably 0.02% or more, and more preferably 0.03% or more. On the other hand, if the Nb content exceeds 0.10%, the carbides become coarse and the hydrogen embrittlement resistance of the steel material decreases. Therefore, when Nb is contained, the Nb content is set to 0.10% or less. In order to reduce the alloy cost, the Nb content is preferably set to 0.08% or less, 0.06% or less, or 0.04% or less.

[0041] V: 0~1.00% V is an element that forms fine carbides in steel and improves the hydrogen embrittlement resistance of the steel material due to the grain refining effect and hydrogen trapping effect of the carbides. Therefore, V may be contained. To obtain the above effects, the V content is preferably 0.01% or more, and more preferably 0.10% or more. However, if the V content exceeds 1.00%, the above effects are saturated and the economic efficiency decreases. Therefore, when V is contained, the V content is set to 1.00% or less. In order to reduce the alloy cost, the V content is preferably set to 0.50% or less, 0.30% or less, or 0.20% or less.

[0042] Ca: 0 to 0.010% Ca is an element that has the effect of refining inclusions in steel and increasing the hydrogen embrittlement resistance of the steel material after quenching. Therefore, Ca may be contained. To obtain the above effects, the Ca content is preferably 0.001% or more, and more preferably 0.002% or more. On the other hand, if the Ca content exceeds 0.010%, the effect is saturated and the cost increases. Therefore, when Ca is contained, the Ca content is set to 0.010% or less. The Ca content is preferably set to 0.005% or less, and more preferably set to 0.004% or less or 0.003% or less.

[0043] Magnesium: 0 to 0.010% Mg is an element that has the effect of refining inclusions in steel and improving toughness after heat treatment. Therefore, Mg may be contained. To obtain the above effects, the Mg content is preferably 0.001% or more. The Mg content is more preferably 0.002% or more. On the other hand, if the Mg content exceeds 0.010%, the effect is saturated and the cost increases. Therefore, when Mg is contained, the Mg content is set to 0.010% or less. The Mg content is preferably 0.005% or less, and more preferably 0.004% or less.

[0044] Al: 0-1.00% Al is an element that is generally used as a deoxidizer for steel. Therefore, Al may be contained. In order to obtain the above effects, the Al content is preferably 0.01% or more. On the other hand, if the Al content exceeds 1.00%, the above effects are saturated and the economic efficiency decreases. Therefore, when Al is contained, the Al content is set to 1.00% or less. In order to reduce the alloy cost, the Al content is preferably set to 0.50% or less, 0.30% or less, 0.10% or less, 0.06% or less, or 0.04% or less.

[0045] Sn: 0 to 1.00% Sn is an element that stabilizes a protective film in a corrosive environment and improves corrosion resistance. Therefore, it is preferable to contain Sn. If the Sn content is less than 0.01%, these effects are not sufficient, so when Sn is contained, the Sn content is preferably 0.01% or more. The Sn content is more preferably 0.03% or more, and even more preferably 0.05% or more. However, if the Sn content exceeds 1.00%, the grain boundary strength decreases, and the hydrogen embrittlement resistance of the steel material after quenching decreases. Therefore, when Sn is contained, the Sn content is set to 1.00% or less. In order to reduce the alloy cost, the Al content is preferably set to 0.50% or less, 0.30% or less, 0.10% or less, 0.06% or less, or 0.04% or less.

[0046] W: 0~1.00% W is an element effective for improving the hardenability of steel and stably ensuring the strength of the steel material after hardening. Therefore, W may be contained. W is also an element that improves corrosion resistance in a corrosive environment. In order to obtain the above effects, the W content is preferably 0.01% or more. On the other hand, if the W content exceeds 1.00%, the above effects are saturated and the economic efficiency decreases. Therefore, when W is contained, the W content is set to 1.00% or less. In order to reduce the alloy cost, the W content is preferably set to 0.50% or less, 0.30% or less, 0.10% or less, 0.06% or less, or 0.04% or less.

[0047] Sb: 0 to 1.00% Sb is an element that improves corrosion resistance in a corrosive environment. Therefore, Sb may be contained. In order to obtain the above effects, the Sb content is preferably 0.01% or more. On the other hand, if the Sb content exceeds 1.00%, the grain boundary strength decreases, and the hydrogen embrittlement resistance of the steel material after quenching decreases. Therefore, when Sb is contained, the Sb content is set to 1.00% or less. In order to reduce the alloy cost, the Sb content is preferably set to 0.50% or less, 0.30% or less, 0.10% or less, 0.06% or less, or 0.04% or less.

[0048] Zr: 0 to 1.00% Zr is an element that improves corrosion resistance in a corrosive environment. Therefore, Zr may be contained. In order to obtain the above effects, the Zr content is preferably 0.01% or more. On the other hand, if the Zr content exceeds 1.00%, the grain boundary strength decreases, and the hydrogen embrittlement resistance of the steel material after quenching decreases. Therefore, when Zr is contained, the Zr content is set to 1.00% or less. In order to reduce the alloy cost, the Zr content is preferably set to 0.50% or less, 0.30% or less, 0.10% or less, 0.06% or less, or 0.04% or less.

[0049] Co: 0 to 1.00% Co is an element that improves corrosion resistance in a corrosive environment, and therefore Co may be contained. In order to obtain the above effects, the Co content is preferably 0.01% or more. On the other hand, if the Co content exceeds 1.00%, the above effects are saturated and the economic efficiency decreases. Therefore, when Co is contained, the Co content is set to 1.00% or less. In order to reduce the alloy cost, the Co content is preferably set to 0.50% or less, 0.30% or less, 0.10% or less, 0.06% or less, or 0.04% or less.

[0050] REM: 0~0.30% Like Ca, REM is an element that refines inclusions in steel and improves the hydrogen embrittlement resistance of the steel after quenching. Therefore, REM may be contained. To obtain the above effect, the REM content is preferably 0.01% or more, and more preferably 0.02% or more. On the other hand, if the REM content exceeds 0.30%, the effect saturates and the cost increases. Therefore, if REM is contained, the REM content is set to 0.30% or less. The REM content is preferably set to 0.20% or less, 0.10% or less, or 0.04% or less.

[0051] Here, REM refers to a total of 17 elements including Sc, Y, and lanthanides such as La and Nd, and the content of REM means the total content of these elements. REM is added to molten steel using, for example, an Fe-Si-REM alloy, which contains, for example, La, Nd, Ce, and Pr.

[0052] In the chemical composition of the steel plate substrate 11 included in the steel material 1 according to this embodiment, the elements other than those described above, that is, the balance, are Fe and impurities. Here, "impurities" refer to components that are mixed in due to various factors in raw materials such as ores and scraps and the manufacturing process when industrially manufacturing steel plate, and are acceptable within a range that does not adversely affect the characteristics of the steel material according to this embodiment.

[0053] The chemical composition of the steel sheet substrate 11 can be determined by the following method. It can be obtained by performing element analysis by a general method such as ICP-AES from a position 1 / 4 of the plate thickness from the surface ((1 / 4) thickness position) in the plate thickness direction of the steel plate substrate 11. C and S can be measured using the combustion-infrared absorption method, N can be measured using the inert gas fusion-thermal conductivity method, and O can be measured using the inert gas fusion-non-dispersive infrared absorption method.

[0054] Internal structure of steel sheet base material The internal structure (metal structure) of the steel plate substrate 11 of the steel material 1 according to this embodiment is not limited, but in order to obtain a tensile strength of more than 1.5 GPa, the structure is mainly composed of high-strength martensite. Preferably, the area fraction is 70% or more of martensite. More preferably, it is 80% or more or 90% or more. Martensite may be 100%. If the area fraction of martensite is small, it becomes difficult to obtain a tensile strength of more than 1.5 GPa.

[0055] The internal structure of the steel sheet substrate 11 may contain retained austenite, bainite, ferrite, and / or pearlite as the remainder other than martensite. For example, the total area fraction of martensite and bainite may be 90% or more. The total area fraction of martensite and bainite is preferably 92% or more, 95% or more, or 98% or more. The total area fraction of martensite and bainite may be 100%. In addition to so-called fresh martensite, martensite also includes tempered martensite and auto-tempered martensite. Auto-tempered martensite is tempered martensite that is generated during cooling at the time of quenching without performing heat treatment for tempering, and is generated by tempering the generated martensite in situ due to self-heating associated with martensitic transformation.

[0056] The structure fraction in the internal structure of the steel sheet substrate 11 can be measured by the following method. The area fraction of martensite (including tempered martensite and auto-tempered martensite) is measured using a transmission electron microscope (TEM) and an electron beam diffraction device attached to the TEM. A measurement sample is cut out from a position 10 mm or more away from the end of the steel plate substrate (or from the center if the width or length of the steel plate substrate is less than 20 mm) and at a position that is 1 / 4 the thickness of the steel plate substrate, and used as a thin film sample for TEM observation. 2 The range is observed by TEM. The electron diffraction patterns of thin film samples are used to distinguish between martensite and bainite, which are body-centered cubic lattices, and retained austenite, which is a face-centered cubic lattice. Iron carbide (Fe3C) in martensite and bainite is then identified from the diffraction patterns, and the structure fractions of martensite and bainite are measured by observing their precipitation morphology. Specifically, if the precipitation morphology is three-directional precipitation, it is determined to be martensite, and if it is limited to one direction, it is determined to be bainite. The structure fractions of martensite and bainite measured by TEM are measured as area percentages, but since the steel material according to this embodiment has an isotropic metal structure, the value of the area fraction can be directly replaced with the volume fraction. Carbides are observed to distinguish between martensite and bainite, but in this embodiment, carbides are not included in the measurement of the structure fraction. When ferrite or pearlite is present as the remaining structure, it can be easily confirmed with an optical microscope or a scanning electron microscope. Specifically, a measurement sample is cut out from a position 10 mm or more away from the end of the steel plate substrate (or from the center if the width or length of the steel plate substrate is less than 20 mm) and including a position at (1 / 4) the thickness of the steel plate substrate, and used as the sample for observation. The cut sample is mechanically polished and then mirror-finished. The sample is then etched with a nital etchant to reveal the ferrite and pearlite, and a 40,000 μm2 area specimen is then examined using a scanning electron microscope. 2 The presence of ferrite or pearlite is confirmed by observing the range of ferrite and cementite. Pearlite is a structure in which ferrite and cementite are arranged in alternating layers, while bainite is a structure in which cementite precipitates in granular form.

[0057] Coating of steel substrate A coating (corrosion-resistant coating) 13 may be provided on a part of the surface of the steel sheet substrate 11 provided in the steel material 1 according to this embodiment. The coating (corrosion-resistant coating) 13 may be a coating mainly made of Al-Fe (Al-Fe-based coating) or a coating mainly made of Zn-Fe (Zn-Fe-based coating). The coating is also called a film, an alloyed plating layer, or an intermetallic compound layer. In a state before being subjected to the heat treatment (C1) described later, which corresponds to the heat treatment of hot stamping (for example, the state of the steel sheet before hot stamping), the steel sheet is a plated steel sheet having a "plating layer" such as an Al-based plating or a Zn-based plating. The plating layer in the state of the steel sheet before hot stamping does not necessarily have to be an alloyed plating layer, and may be a (non-alloyed) plating layer. However, in the steel material 1 (for example, a hot stamped body) after being subjected to the heat treatment (C1) described later, even if the plating is not an alloyed plating in the state of the steel sheet, it is alloyed by the subsequent heat treatment (C1), and the plating layer (i.e., the coating) becomes an alloyed plating layer. The alloyed plating layer may simply be called a plating layer, and the coating of the steel material 1 may simply be called a plating layer.

[0058] The coating mainly composed of Al-Fe in the steel material 1 is a coating having an average chemical composition of the entire coating containing 70 mass % or more of Fe and Al in total. In addition to Fe and Al, the coating may further contain Si, Mg, Ca, Sr, Ni, Cu, Mo, Mn, Cr, C, Nb, Ti, B, V, Sn, W, Sb, Zn, Co, In, Bi, Zr, Se, As, and REM, and the remainder may be impurities. The coating mainly composed of Zn-Fe in the steel material 1 is a coating having an average chemical composition of the entire coating containing 70 mass % or more of Fe and Zn in total. In addition to Fe and Zn, the coating may further contain Si, Mg, Ca, Sr, Ni, Cu, Mo, Mn, Cr, C, Nb, Ti, B, V, Sn, W, Sb, Al, Co, In, Bi, Zr, Se, As, and REM, and the remainder may be impurities.

[0059] (A2) Protective film The steel material 1 according to this embodiment has a protective film 12 on at least a part of the surface of the above-mentioned steel plate substrate 11. The protective film 12 contains a large amount of Fe3O4, and in an X-ray analysis (X-ray diffraction method) measured using CuKα radiation, the protective film 12 has a peak at a diffraction angle (2θ) of 35.5±0.5°, the peak intensity of which exceeds 250%, assuming that the peak intensity at a diffraction angle (2θ) of 36.6±0.5° is 100%. By forming this protective film 12 on the surface of the steel plate substrate 11, the corrosion resistance of the steel material 1 is improved. Here, the substance with a diffraction angle (2θ) of around 35.5° is Fe3O4 (magnetite), and the substance with a diffraction angle (2θ) of around 36.6° is FeOOH (iron (III) oxyhydroxide), with 35.5° and 36.6° being the main peak positions of the respective substances. This means that the protective film 12 provided on the steel material 1 according to this embodiment has a higher volume fraction of Fe3O4 than FeOOH. (±0.5° is a tolerance taking into account measurement errors, etc.) Since Fe3O4 has a higher density than FeOOH, it is believed that by increasing the proportion of Fe3O4, which has a higher density, the protective film 12 becomes denser, hydrogen generation in a corrosive environment is suppressed, and resistance to hydrogen embrittlement is improved. In the X-ray analysis of protective film 12 measured using CuKα radiation as described above, if the peak intensity at a diffraction angle (2θ) of 36.6±0.5° is taken as 100%, and the peak intensity at a diffraction angle (2θ) of 35.5±0.5° is 250% or less, the volume fraction of Fe3O4 in protective film 12 is small, and protective film 12 does not provide a sufficient effect of improving corrosion resistance. In the steel material 1 according to this embodiment, the protective film 12 is a film mainly composed of iron oxide or iron oxyhydroxide, and preferably contains a total of 70 mass% or more of Fe, O, and H. In addition to Fe, O, and H, the protective film 12 may further contain the components of the steel sheet substrate 11 described above, that is, Si, Mg, Ca, Sr, Ni, Cu, Mo, Mn, Cr, C, Nb, Ti, B, V, Sn, W, Sb, Zr, REM, and Zn.

[0060] When the steel material 1 according to this embodiment is provided with a corrosion-resistant coating 13, the protective film 12 having excellent corrosion resistance as described above is formed on the surface of the steel plate substrate 11 at a position where the corrosion-resistant coating 13 is not present. That is, in this case, the steel plate substrate 11 has a portion on its surface that is provided with the corrosion-resistant coating 13 and a portion on its surface that is provided with the protective film 12. For example, if the steel material 1 is obtained by cutting a steel plate having a corrosion-resistant coating 13, the corrosion-resistant coating 13 is not present on the cut end surface. Therefore, the steel material 1 can be formed with the protective film 12 formed on the surface of the cut end surface and the corrosion-resistant coating 13 formed on the other surface (see, for example, FIG. 2). When the steel material 1 does not have a corrosion-resistant coating 13 , the protective film 12 may be formed on the entire surface of the steel sheet substrate 11 . The thickness of the protective film 12 is not particularly limited, but is preferably 5 μm or more in order to obtain a sufficient effect of improving corrosion resistance. On the other hand, if the thickness of the protective film 12 exceeds 300 μm, it becomes difficult to ensure sufficient strength as a steel material. Therefore, the thickness of the protective film 12 is preferably 300 μm or less.

[0061] In the steel material according to the present embodiment, it is preferable that Cu is concentrated in the protective film. Specifically, it is preferable that the ratio of the maximum Cu content in the protective film to the Cu content in the steel sheet substrate (maximum Cu content in protective film / Cu content in steel sheet substrate: Cu concentration ratio) is 1.5 or more, 1.7 or more, 1.9 or more, or 2.1 or more. The protective film with concentrated Cu is uniform, dense, and stable, which contributes to further improving corrosion resistance. If the ratio of the maximum Cu content in the protective film to the Cu content in the steel sheet substrate is less than 1.5, sufficient effects cannot be obtained. The upper limit of the ratio of the maximum Cu content in the protective film to the Cu content in the steel sheet substrate does not need to be particularly set, but may be 5.0. If necessary, the upper limit of the ratio may be 4.5, 4.0, 3.5, 3.0, or 2.8.

[0062] The intensities of the peak at the diffraction angle of 35.5±0.5° and the peak at the diffraction angle of 36.6±0.5° in the protective film 12 are determined by X-ray diffraction (XRD). For the measurement, a fully automatic multipurpose X-ray diffractometer (SmrtLab 3kW manufactured by Rigaku Co., Ltd.) is used, and measurements are performed at a time interval of 2° / min using CuKα radiation to determine the diffraction angle (2θ) up to 90°, and the intensities of the peak at the diffraction angle of 35.5±0.5° and the peak at the diffraction angle of 36.6±0.5° are determined. When the peak intensities are determined, the diffraction profile is fitted using a pseudo-Voigt function using SmartLab Studio II manufactured by Rigaku Co., Ltd. as software, and the number of peak counts is taken as the peak intensity. In addition, B-spline interpolation is performed as the background, and the peak intensity obtained by subtracting this value is used. From this result, the ratio of the peak intensity at a diffraction angle (2θ) of 36.6±0.5° to the peak intensity at a diffraction angle (2θ) of 35.5±0.5° can be calculated. Other peaks resulting from the presence of Fe3O4 or FeOOH obtained from the protective film 12 may include those at diffraction angles (2θ) of 11°, 14°, 16°, 21°, 26°, 27°, 30°, 31°, 33°, 34°, 39°, 41°, 43°, 50°, 53°, 55°, 57°, 58°, 61°, 62°, 63°, 71°, 75°, and 83°. However, most of these peaks have lower intensity than the peaks at around 35.5° and 36.6°. Therefore, it is not necessary to measure the intensity of peaks other than those at around 35.5° and 36.6°.

[0063] The maximum Cu content in the protective film is determined by subjecting the protective film 12 to GDS (glow discharge optical emission spectroscopy). Specifically, GDS (glow discharge optical emission spectroscopy) is performed from the surface of the protective film in the thickness direction to determine the maximum Cu content in the range from the surface of the protective film to the interface between the protective film and the steel sheet substrate. This measurement is performed five times, and the average of the maximum Cu contents obtained in each measurement is taken as the maximum Cu content in the protective film. During the measurement, since impurities may be attached to the protective film, the Fe content and O content are also measured, and the position where the total content of Fe and O is 85% is taken as the surface of the protective film. The position where the Fe content is 95% is taken as the interface between the protective film and the steel sheet substrate.

[0064] (A3) Characteristics of steel In the steel material 1 according to this embodiment, the protective film 12 is controlled as described above, so that corrosion is reduced and hydrogen penetration due to corrosion is suppressed. Therefore, the steel material 1 according to this embodiment has excellent resistance to hydrogen embrittlement in a corrosive environment. In addition, the steel material 1 according to this embodiment has high strength, with a tensile strength exceeding 1500 MPa (1.5 GPa). The tensile strength of the steel material 1 according to this embodiment is preferably 1800 MPa or more. Although there is no upper limit to the tensile strength, as the moldability and processability decrease as the tensile strength increases, the tensile strength may be set to 3200 MPa or less, 3000 MPa or less, or 2800 MPa or less. When the steel material is a tailored property material having different strengths depending on the location, as described below, it is sufficient that at least a part of the steel material has a tensile strength of more than 1500 MPa.

[0065] In this embodiment, hydrogen embrittlement resistance in a corrosive environment is evaluated by an exposure test in the actual use environment of the steel material or an accelerated corrosion test by CCT (combined cyclic test). For example, the steel material is subjected to four-point bending to be exposed outdoors while being stressed, and is evaluated based on whether or not it cracks for a certain period of time.

[0066] The shape of the steel material 1 according to this embodiment is not particularly limited. That is, the steel material 1 is a steel plate member obtained by heat treatment (including processing during cooling of the heat treatment) of a steel plate, which is a material for the steel material 1, and the shape may be a flat plate or a formed body (or a hot stamp formed body). Hot-formed steel is often a formed body. However, in this embodiment, both the formed body and the flat plate are referred to as "steel material". In addition, the steel material may be a tailored property material having different strengths depending on the location. In this case, it is preferable that at least a part of the steel material has a tensile strength of 1.5 GPa or more. By obtaining a region with different strengths, it is possible to control the deformation of a portion having a tensile strength of more than 1500 MPa during a collision, and it is possible to protect occupants more safely.

[0067] (B) Steel plate material Next, a steel plate (hereinafter, sometimes referred to as the steel plate according to the present embodiment) that is the material of the steel plate substrate 11 included in the steel material 1 according to the present embodiment will be described. The steel plate described below is subjected to a heat treatment described later to obtain the steel plate substrate 11.

[0068] Chemical composition of steel plate The range of the chemical composition of the steel plate according to this embodiment is the same as that of the steel plate substrate 11 of the steel material 1 according to this embodiment described above, and the reasons for the limitations are also the same. The chemical composition of a steel sheet is obtained, for example, by performing element analysis at a representative position, which is a quarter of the sheet thickness from the surface of the steel sheet in the sheet thickness direction, using a general method such as ICP.

[0069] Internal structure of steel plate The internal structure (metal structure) of the steel plate according to the present embodiment is not limited, but is often ferrite or pearlite. Bainite, martensite, and retained austenite may be contained within the conditions of the manufacturing method described below. The martensite includes tempered martensite and auto-tempered martensite. Auto-tempered martensite is tempered martensite that is generated during cooling at the time of quenching without performing heat treatment for tempering, and is generated by tempering the generated martensite in situ due to heat generation associated with martensitic transformation. The internal structure of the steel plate is the structure of the steel plate excluding the above-mentioned boundary portion. The internal structure of the steel sheet can be determined in the same manner as the internal structure of the steel sheet substrate 11 described above.

[0070] Next, a method for manufacturing the steel material 1 according to this embodiment will be described.

[0071] (C) Steel manufacturing method The steel material 1 according to this embodiment can be manufactured by a manufacturing method including the following steps. (C1) a heat treatment step of heat treating a steel plate having a predetermined chemical composition to obtain a steel plate substrate 11; (C2) A protective film stabilization treatment step of forming a protective film 12 on the steel sheet substrate 11 and stabilizing the protective film 12. Each step will be described below.

[0072] (C1) <Heat treatment process> In the heat treatment step, a steel sheet having a predetermined chemical composition is heat treated to produce a steel sheet substrate 11. The heat treatment is carried out under conditions in which, for example, a steel sheet obtained by a method described below is heated to a temperature between Ac3 point and (Ac3 point + 300) °C at an average heating rate of 1.0 to 1000 °C / sec, and then cooled to a temperature below the Ms point (°C) at an average cooling rate equal to or higher than the upper critical cooling rate. If the heating rate is less than 1.0°C / sec, the productivity of the heat treatment decreases, which is not preferable, whereas if the heating rate exceeds 1000°C / sec, a duplex structure is formed and the limit hydrogen content decreases, which is not preferable. Furthermore, if the heat treatment temperature is less than the Ac3 point (°C), ferrite will remain after cooling, resulting in insufficient strength, which is undesirable, whereas if the heat treatment temperature is more than the Ac3 point + 300°C, the structure will become coarse-grained, reducing the limit hydrogen content, which is undesirable. The upper critical cooling rate is the minimum cooling rate at which austenite is supercooled to form martensite without precipitating ferrite or pearlite in the structure. If cooling is performed below the upper critical cooling rate, ferrite and pearlite will form, resulting in insufficient strength. During heating, the temperature may be held within a range of ±10° C. of the heating temperature for 1 to 300 seconds. After cooling to a temperature equal to or lower than the Ms point, the steel material may be subjected to a tempering treatment in a temperature range of about 100 to 600° C. in order to adjust the strength of the steel material.

[0073] The Ac3 point, Ms point and upper critical cooling rate are measured by the following method. A rectangular test piece having a width of 30 mm and a length of 200 mm is cut out from the steel plate according to this embodiment, and the test piece is heated to 1000°C in a nitrogen atmosphere at a heating rate of 10°C / sec, and is held at that temperature for 5 minutes, and then cooled to room temperature at various cooling rates. The cooling rate is set at intervals of 10°C / sec from 1°C / sec to 100°C / sec (however, the rate after 1°C / sec is 10°C / sec). The Ac3 point and Ms point are measured by measuring the change in thermal expansion of the test piece during heating and cooling. In addition, among the test pieces cooled at the above cooling rates, the minimum cooling rate at which no ferrite phase precipitation occurs is defined as the upper critical cooling rate.The Ms point obtained from the change in thermal expansion when cooled at or above the upper critical cooling rate is defined as the Ms point of the steel material.

[0074] Here, in the above series of heat treatments, after heating to a temperature range of Ac3 point to (Ac3 point + 300) ° C., while cooling to the Ms point, that is, at or above the upper critical cooling rate, hot forming such as hot stamping may be performed at the same time. Examples of hot forming include bending, drawing, stretching, hole expansion, and flange forming. In addition, the present invention may be applied to forming methods other than press forming, such as roll forming, as long as a means for cooling the steel sheet simultaneously with or immediately after forming is provided. If the above thermal history is followed, repeated hot forming may be performed.

[0075] As described above, the steel material according to the present embodiment includes both a steel sheet that has been hot-formed into a formed body and a steel sheet that has been subjected to only heat treatment and is in the form of a flat plate.

[0076] Furthermore, as the steel material according to this embodiment, hot forming or heat treatment may be performed on a part of the steel plate serving as the raw material to obtain a steel material having regions with different strengths.

[0077] The above series of heat treatments can be carried out by any method, and for example, the heating may be carried out by high-frequency heating, electrical heating, infrared heating, or furnace heating, and the cooling may be carried out by water cooling, mold cooling, or the like.

[0078] (C2) <Protective film stabilization process> In the protective film stabilization treatment process, a corrosion acceleration test is used to form a protective film 12 on the surface of a steel sheet substrate 11 on which a corrosion-resistant coating 13 is not formed, and the formed protective film 12 is stabilized. Iron oxide serving as the base of the protective film 12 is formed on the steel sheet substrate 11 obtained in the above-mentioned heat treatment process, and the protective film 12 can be formed and stabilized by a combined cycle of salt spray, wetting, and drying. Specifically, in the combined cycle, the salt concentration (concentration of salt water) is set to 1 to 10%, the wet ratio ((salt spray time + wetting time) / total time) is set to 30 to 70%, one cycle is set to 8 hours, and the number of cycles is set to 30 to 100, whereby the protective film 12 containing a large amount of Fe3O4 can be formed and stabilized. Each condition will be explained below.

[0079] Salt concentration: 1-10% In the protective film stabilization treatment, the protective film 12 is formed by a reaction between the surface of the steel sheet substrate 11 and the chlorides in the sprayed salt water. In order to stabilize the protective film 12, a salt concentration of 1 to 10% is suitable. If the salt concentration is less than 1%, the protective film may be formed non-uniformly, which is not preferable. On the other hand, if the salt concentration exceeds 10%, the corrosion rate is high and the protective film 12 may not be formed stably, which is not preferable.

[0080] Wet rate: 30~70% In the protective film stabilization treatment, the protective film 12 is formed by a surface reaction with chloride. In order to stabilize the protective film 12, a wet ratio of 30 to 70% is suitable. If the wet ratio is less than 30%, the corrosion rate is high and the protective film 12 may not be formed stably, which is not preferable. On the other hand, if the wet ratio is more than 70%, the protective film 12 may be formed non-uniformly, which is not preferable.

[0081] Number of cycles: 30 to 100 cycles (8 hours per cycle) In the protective film stabilization treatment, the protective film 12 is formed by repeating cycles of salt spray, wetting, and drying. If the number of cycles is less than 30, the protective film 12 may not be sufficiently formed, which is not preferable. From the viewpoint of forming the protective film 12, it is not necessary to specify an upper limit of the number of cycles, but if the number of cycles is excessive, the protective film may peel off and the desired protective film may not be formed, which is not preferable. In addition, the steel material 1 may be thinned, which may reduce its strength as a structure. Therefore, the number of cycles is set to 100 or less.

[0082] In addition, it is preferable not to apply stress to the steel sheet before forming the protective film. In a state where stress is applied, the behavior of the protective film formation varies between the stress-applied portion and other portions, and therefore, even if the above-mentioned protective film stabilization treatment is performed, the protective film may not be stabilized, which is not preferable.

[0083] Moreover, the protective film stabilization treatment is preferably carried out at 100° C. or less. At higher temperatures, oxidation of the steel sheet is preferential, so that the ratio of the maximum Cu content in the protective film to the Cu content in the steel sheet substrate is less than 1.5.

[0084] (D) Steel plate manufacturing method There are no limitations on the method of manufacturing a steel plate suitable as a material for the steel plate substrate 11 included in the steel material 1 according to this embodiment, but it can be manufactured, for example, by using a manufacturing method including the steps shown below. (i) a slab preparation step of melting steel having the above-mentioned chemical composition and casting it to produce a slab; (ii) a hot rolling step in which the obtained slab is hot rolled to obtain a hot rolled steel sheet; (iii) a winding process for winding the hot-rolled steel sheet; (iv) a hot-rolled sheet annealing process, in which the hot-rolled steel sheet after the coiling process is annealed as necessary; (v) a cold rolling step of, as necessary, descaling the hot-rolled steel sheet after the coiling step or the hot-rolled steel sheet annealing step, and cold rolling the same to obtain a cold-rolled steel sheet; (vi) an annealing step of annealing the hot-rolled steel sheet or the cold-rolled steel sheet as necessary to obtain an annealed steel sheet; (vii) If necessary, a coating step of applying a corrosion-resistant coating to the hot-rolled steel sheet, the cold-rolled steel sheet or the annealed steel sheet to obtain a coated steel sheet.

[0085] Each step will be described below.

[0086] <Slab preparation process> In the slab preparation process, a steel having the above-mentioned chemical composition is melted and cast to produce a slab to be subjected to hot rolling. For example, a slab produced by melting molten steel having the above-mentioned chemical composition using a converter or an electric furnace and producing the slab by a continuous casting method can be used. Instead of the continuous casting method, an ingot casting method, a thin slab casting method, or the like may be adopted.

[0087] <Hot rolling process> In the hot rolling process, the slab is heated, roughly rolled, descaled if necessary, and finally finished rolled. There are no limitations on the hot rolling conditions.

[0088] <Winding process> In the coiling process, for example, the hot-rolled steel sheet after the hot rolling process is coiled at a temperature range of 800° C. or less. If the coiling temperature exceeds 800° C., the steel sheet is coiled before transformation has progressed much, and the transformation progresses in the coil, which may result in a defective coil shape, which is not preferable.

[0089] <Hot-rolled sheet annealing process> In the annealing process of the hot-rolled steel sheet, annealing is performed for 5 hours or more at 450 to 800°C in an atmosphere of 80% by volume or more of nitrogen or in air as necessary. Annealing of the hot-rolled steel sheet is preferable because it softens the hot-rolled steel sheet and reduces the load in the subsequent cold rolling process.

[0090] <Cold rolling process> In the cold rolling step, if necessary, the hot-rolled steel sheet after the hot-rolled sheet annealing step (the hot-rolled steel sheet after the coiling step when the hot-rolled sheet annealing step is not performed) is descaled and cold-rolled to obtain a cold-rolled steel sheet. Descaling and cold rolling are not necessarily required, but when cold rolling is performed, the cumulative reduction in cold rolling is preferably 30% or more from the viewpoint of ensuring good flatness. On the other hand, in order to avoid an excessive rolling load, the cumulative reduction in cold rolling is preferably 80% or less. The method of descaling is not particularly limited, but pickling is preferred. When pickling is performed, it is preferred to remove only iron scale by pickling with hydrochloric acid or sulfuric acid.

[0091] <Annealing process> In the annealing step before coating, the hot-rolled steel sheet or the cold-rolled steel sheet is annealed in a temperature range of 700 to 950° C. as necessary to obtain an annealed steel sheet. The annealing step is preferable because it softens the cold-rolled steel sheet and makes it easier to pass the sheet in the subsequent plating step.

[0092] <Coating process> In the coating process, a coating (corrosion-resistant coating that contributes to improving corrosion resistance) is formed on the surface of a steel sheet (a hot-rolled steel sheet after a coiling process, a hot-rolled steel sheet after a hot-rolling annealing process, a cold-rolled steel sheet after a cold-rolling process, or an annealed steel sheet after an annealing process) as necessary to produce a coated steel sheet. The method of the corrosion-resistant coating is not particularly limited, and may be a hot-dip galvanizing method, an electroplating method, a vacuum deposition method, a cladding method, a thermal spraying method, or the like. The hot-dip galvanizing method is the most widely used method industrially. Examples of coatings that contribute to improving corrosion resistance include Al-based coatings that contain Al and Zn-based coatings that contain Zn. In the case of an Al-based coating, the Al is partially or entirely alloyed with the Fe in the steel sheet by heat treatment to become an Al-Fe-based coating, while in the case of a Zn-based coating, the Zn is partially or entirely alloyed with the Fe in the steel sheet by heat treatment to become a Zn-Fe-based coating.

[0093] When forming an Al-based coating by hot-dip plating, the plating bath often contains Fe as an impurity in addition to Al. In addition to the above elements, the plating bath may contain Si, Mg, Ca, Sr, Ni, Cu, Mo, Mn, Cr, C, Nb, Ti, B, V, Sn, W, Sb, Zn, Co, In, Bi, Zr, Se, As, misch metal, etc., so long as it contains 70 mass% or more of Al. When hot-dip plating is performed, the annealed steel sheet after the annealing process may be cooled to room temperature and then heated again to perform plating, or may be cooled to 650 to 750 ° C., which is close to the plating bath temperature, after annealing, and hot-dip plating may be performed without cooling to room temperature. When a Zn-based coating is formed by hot-dip plating, the plating bath often contains Fe as an impurity in addition to Zn. In addition to the above elements, the plating bath may contain Si, Mg, Ca, Sr, Ni, Cu, Mo, Mn, Cr, C, Nb, Ti, B, V, Sn, W, Sb, Zn, Co, In, Bi, Zr, Se, As, misch metals, etc., as long as the plating bath contains 70 mass% or more of Zn. When hot-dip plating is performed, the annealed steel sheet after the annealing process may be cooled to room temperature and then heated again to perform plating, or may be cooled to 400 to 600°C, which is close to the plating bath temperature, after annealing, and then hot-dip plating may be performed without cooling to room temperature.

[0094] There is no particular limitation on the pre-treatment or post-treatment of the corrosion-resistant coating, and it is possible to perform pre-coating, solvent coating, alloying, temper rolling, etc. As the alloying treatment, for example, annealing at 450 to 800° C. is possible. As the post-treatment, temper rolling is useful for shape adjustment, etc., and for example, reduction of 0.1 to 0.5% is possible. EXAMPLES

[0095] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0096] Steels having the chemical compositions shown in Tables 1-1 and 1-2 (continuation of Table 1-1) were melted to obtain slabs. The obtained slab was subjected to hot rolling and coiled at a temperature of 800° C. or less to obtain a hot-rolled steel sheet having a thickness of 3.2 mm. The hot-rolled steel sheets except for B35 to B37 were pickled and then cold-rolled to obtain cold-rolled steel sheets having a thickness of 1.6 mm. Some of the steel sheets (B38 to 40) were subjected to hot-rolled annealing before pickling at 700°C for 12 hours. In addition, for some of the steel sheets (B41 to B43), after cold rolling, the steel sheets were heated to 760°C for annealing, and further immersed in an Al plating bath at 680°C containing 10% Si, 2% Fe, and the balance being impurities to produce aluminized steel sheets. In addition, some of the steel sheets (B44 to B469) were cold-rolled and then immersed in a Zn-plating bath at 470° C. to obtain Zn-plated steel sheets. The chemical composition of these steel plates (hot-rolled steel plate, cold-rolled steel plate, coated steel plate) was measured at a position 1 / 4 of the plate thickness from the surface, and the results were the same as the chemical composition of the slab.

[0097] [Table 1-1]

[0098] [Table 1-2]

[0099] From the obtained steel plates, steel plates of 200 mm x 50 mm (x plate thickness) and 68 mm x 8 mm (x plate thickness) were cut out, and these steel plates were heated to the heating temperatures shown in Tables 2-1 and 2-2 at the average heating rate shown in Tables 2-1 and 2-2, held at a temperature within ±10°C of this heating temperature for 60 seconds, and then cooled to a temperature below the Ms point at the average cooling rate shown in Tables 2-1 and 2-2, thereby obtaining steel materials B1 to B46 and b1 to b50. The chemical composition of the 200 mm x 50 mm steel plate substrate that had been subjected to the above-mentioned heat treatment at a position 1 / 4 of the plate thickness from the surface in the plate thickness direction was the same as that of the slab. The martensite area ratio in the internal structure of the 200 mm x 50 mm steel material that had been subjected to the heat treatment was determined in the same manner as described above. The results are shown in Tables 2-3 and 2-4. The remainder of the internal structure was one or more of retained austenite, bainite, ferrite, and pearlite.

[0100] The 200 mm x 50 mm and 68 mm x 8 mm steel materials that had been subjected to the above-mentioned heat treatment were subjected to a protective film stabilization treatment at room temperature with the salt concentration, wet rate, and number of cycles (1 cycle 8 hours) shown in Tables 2-1 and 2-2, to obtain steel materials with a protective film. However, in the case of examples in which an Al-Fe-based coating or a Zn-Fe-based coating was formed on the surface, a protective film stabilization treatment was performed on the surface exposed by cutting (where no Al-Fe-based coating or Zn-Fe-based coating was formed).

[0101] In the obtained steel material, X-ray diffraction, tensile test, and exposure test were conducted in the following manner. When the peak intensity at the position where the diffraction angle of the protective film was 36.6 ± 0.5° was taken as 100%, the peak intensity (relative intensity of the peak intensity in the table) at the position where the diffraction angle was 35.5 ± 0.5°, the tensile strength, and the hydrogen embrittlement resistance in the corrosive environment were evaluated. The evaluation results are shown in Tables 2-3 and 2-4.

[0102] <X-ray diffraction> For the protective film of the steel material, using CuKα radiation under the condition of 2° / min, the peak intensity at the position where the diffraction angle (2θ) was 35.5 ± 0.5° and the peak intensity at the position where the diffraction angle was 36.6 ± 0.5° were determined. When the peak intensity at the position of 36.6 ± 0.5° was taken as 100%, the peak intensity (relative intensity) at the position of 35.5 ± 0.5° was determined. For peak intensity calculation, the diffraction profile was fitted using the pseudo-Voigt function to obtain the peak count number, B-spline interpolation was performed as the background, and the value was subtracted to obtain the peak intensity. For X-ray diffraction measurement, SmartLab 3kW manufactured by Rigaku was used, and profile fitting was performed using SmartLab Studio II manufactured by the same Rigaku.

[0103] <Tensile strength> The tensile test was carried out in accordance with the provisions of ASTM standard E8. After grinding the 200mm×50mm steel material subjected to the above heat treatment and protective film stabilization treatment to a thickness of 1.2mm, a half-size plate-shaped test piece (parallel part length: 32mm, parallel part plate width: 6.25mm) of ASTM standard E8 was taken so that the test direction was parallel to the rolling direction. Then, strain gauges (gauge length: 5mm) were attached to the center of the width and length directions of the parallel part of the test piece, and a room temperature tensile test was carried out at a strain rate of 3mm / min to measure the tensile strength (maximum strength). In this example, a case having a tensile strength exceeding 1500MPa was evaluated as having a high strength.

[0104] <Exposure test> Hydrogen embrittlement resistance in a corrosive environment was evaluated by an exposure test of stressed steel. Specifically, a 4-point bending specimen was produced by applying a strain equivalent to 1 / 2 the tensile strength previously determined by the method described below to a 68mm x 8mm steel that had been subjected to the above-mentioned heat treatment and protective film stabilization treatment. Prior to the production of this specimen, a test specimen produced in advance on the same machine was prepared, and a strain gauge (gauge length: 5mm) similar to that used in the tensile test was attached to the center of the width and length of the test specimen to obtain the relationship between the strain and the 4-point bending displacement amount, and the 4-point bending displacement amount that corresponds to a strain equivalent to 1 / 2 the tensile strength was obtained. The 4-point bent test specimen was subjected to an outdoor exposure test (1-1 Tobihata-cho, Tobata-ku, Kitakyushu City) together with a jig, and if no cracks were observed visually after more than one year, it was determined that the specimen had excellent hydrogen embrittlement resistance in a corrosive environment.

[0105] [Table 2-1]

[0106] [Table 2-2]

[0107] [Table 2-3]

[0108] [Table 2-4]

[0109] As shown in Tables 2-1 to 2-4, the invention examples B1 to B46, which satisfy the range of the present invention, have good results in both structure and properties, but the comparative examples b1 to b49, which do not satisfy the range of the present invention, have insufficient chemical composition or protective film formation, and are inferior in at least one of strength and hydrogen embrittlement resistance. In addition, the comparative example b50 could not proceed to the evaluation of the next process because the protective film peeled off during the protective film stabilization treatment. [Explanation of symbols]

[0110] 1 Steel material 11 Steel plate base material 12 Protective film 13 Corrosion-resistant coating (coating)

Claims

1. A steel sheet substrate; A protective film formed on at least a portion of a surface of the steel plate substrate; having The chemical composition of the steel plate substrate is, in mass%, C: 0.25-0.65%, Si: 0.05-2.00%, Mn: 0.30-3.00%, P: 0.050% or less, S: 0.0100% or less, N: 0.010% or less, O: 0.010% or less, Cr: 0.05-1.00%, Cu: 0.10-1.00%, Ti: 0 to 0.10%, B: 0 to 0.0100%, Mo: 0-1.00%, Ni: 0 to 1.00%, Nb: 0 to 0.10%, V: 0-1.00%, Ca: 0-0.010%, Mg: 0 to 0.010%, Al: 0-1.00%, Sn: 0-1.00%, W: 0-1.00%, Sb: 0 to 1.00%, Zr: 0 to 1.00%, Co: 0-1.00%, REM: 0 to 0.30%, and The balance is Fe and impurities. the protective film is mainly composed of iron oxide and iron oxyhydroxide and contains Fe, O, and H in a total amount of 70 mass% or more; In an X-ray analysis of the protective film measured using CuKα radiation, the protective film has a peak at a diffraction angle (2θ) of 35.5±0.5°, the peak intensity of which exceeds 250%, when the peak intensity at a diffraction angle (2θ) of 36.6±0.5° is taken as 100%, and a ratio of a maximum Cu content in the protective film to a Cu content in the steel sheet substrate is 1.5 or more; The tensile strength is greater than 1500 MPa. A steel material characterized by:

2. The protective film is formed on the entire surface of the steel plate base material. The steel material according to claim 1 .

3. A corrosion-resistant coating is formed on a portion of the surface of the steel plate substrate where the protective film is not formed. The steel material according to claim 1 .

4. A corrosion-resistant coating is formed on two surfaces perpendicular to the thickness direction of the steel plate substrate, and a protective film is formed on two surfaces parallel to the thickness direction of the steel plate substrate. The steel material according to claim 3 .

5. The corrosion-resistant coating is an Al—Fe-based coating or a Zn—Fe-based coating; The steel material according to claim 3 or 4, characterized in that

Citation Information

Patent Citations

  • Surface treated steel material having superior resistance to hydrogen induced cracking

    JP1987238378A

  • Manufacturing method for collision reinforcing material for vehicle and collision reinforcing material

    JP2002102980A

  • Steel, and method for manufacturing the same, and steel sheet for quenching treatment

    JP2012001802A

  • Hot-press molded steel sheet member, steel sheet for hot-pressed steel sheet member, and method for producing them

    JP2012180594A

  • Steel having excellent hydrogen induced cracking resistance and method for producing the same

    JP2013237101A